A new species of Messoracarus (Acari: Mesostigmata: Aenictequoidea: Messoracaridae) from Laos - Kontschán, Jenő; Seeman, Owen D. (Zootaxa, 2012)
A new species of the ant-associated family Messoracaridae, Messoracarus schwendingeri sp. nov., is described on thebasis of one female and two males from Laos. A short review of the family is also presented, and a key for identification of its our species.